Profitabilitas, Leverage, Pandemi Covid-19, dan Rentang Waktu Audit dengan Variabel Moderasi Firm Size - Wulandari, Komang Ayu; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2023)
Go public companies listed on the IDX are required to report their financial reports to the Financial Services Authority to avoid delays in financial reporting. The purpose of this study was to empirically test firm size in moderating the effect of profitability, leverage, and the COVID-19 pandemic on audit timeframes in energy sector companies listed on the IDX. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021 with a total of 39 companies obtained using a purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). The research results show that firm size moderates the influence of profitability and the COVID-19 pandemic on the audit time span. However, firm size does not moderate the effect of leverage on the audit time span. Keywords: Profitability; leverage; COVID-19 pandemic; Firm Size; Audit Timeframe